Penguatan Profil Pelajar Pancasila Melalui Pembelajaran Diferensiasi Pada Mata Pelajaran Bahasa Arab Di Madrasah Aliyah Asshohwah Al-Islamiyah Gerung Lombok Barat - Dzakisiraj, Ahmad; Suparmanto, Suparmanto; Fatma, Tia; Rismayani, Dian; Raez, Nadia (Lugatuna : Jurnal Prodi PBA, 2024)
This research aims to determine the strategies for strengthening the Pancasila student profile in students through differentiated learning in the Arabic language subject at MA Assahwah Al-Islamiyyah. The research method used is descriptive qualitative research. Data was collected through observation, interviews, and documentation. The results show that differentiated learning in Arabic language instruction can strengthen the Pancasila student profile, especially in dimensions related to mutual cooperation and critical thinking. The implications of this research can serve as a reference for the development of a learning model that combines differentiated approaches with the reinforcement of Pancasila values in the context of Arabic language learning in similar institutions.